Analisis Kesesuaian Pelaksanaan Pembelajaran Kurikulum 2013 pada Guru SMP dalam bentuk Supervisi - Safri Safri (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
Research has been carried out with the title Analysis of the Conformity of the 2013 Curriculum Learning Implementation for Middle School Teachers in the Form of Supervision. The purpose of the study was to determine the percentage of conformity in the implementation of the 2013 curriculum for junior high school teachers in the form of supervision. This type of research is qualitative by involving one of the teachers of SMPN 4 Liliriaja in implementing learning using the 2013 Curriculum. Data collection is carried out by observing the implementation of the 2013 curriculum learning and reviewing the design of the 2013 curriculum learning implementation. The data obtained are processed qualitatively with the Focus method. Group Discussion (FGD) to determine the percentage of conformity. The results obtained are the percentage of conformity of the learning implementation process with the 2013 curriculum by the teacher by 30% according to learning activities in the 2013 curriculum, 30% according to learning events in the 2013 curriculum, 30% according to the core competencies in the 2013 curriculum. % according to the learning stages in the curriculum 2013, and 3% in accordance with the scientific approach to the 2013 curriculum. Thus, it can be concluded that the level of suitability of implementing the 2013 curriculum for junior high school teachers in the form of supervision is still low.